Zinc-doped antibacterial carbon dots as well as preparation method and application thereof
By doping zinc into carbon dots and combining with hydrogels, the existing carbon dot preparation steps and insufficient antibacterial activity are solved, effective antibacterial and low cytotoxicity for a variety of bacteria is achieved, and wide application prospects for wound healing and antibacterial materials are available.
Patent Information
- Application Number
- CN202411648498.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, fluorescent carbon spots with cumbersome preparation steps, difficulty in obtaining raw materials, insufficient antibacterial activity and potentially high toxicity limit their application in skin wound healing and antibacterial materials.
By dispersing biomass and anhydrous zinc acetate in mass ratio in deionized water, stirring ultrasonicly and hydrothermal reactions, zinc doped with antibacterial carbon dots were obtained. Then, zinc-doped antibacterial carbon dots were dissolved in double distilled water in proportion to synthesize a composite hydrogel.
It has achieved effective antibacterial treatment for Gram-positive and Gram-negative bacteria. It has simple preparation process, low cost and low cytotoxicity. It has a wide range of application prospects in antibacterial materials and the treatment of deep skin lesions, diabetes wounds and burns.
Smart Images

Figure CN119499279A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano functional materials, and in particular relates to zinc-doped antibacterial carbon dots and a preparation method and application thereof. Background Art
[0002] Nanotechnology provides new means for medical diagnosis and treatment in terms of treatment, diagnosis and imaging, and has great advantages in biomedicine. Nanotherapeutics have become potential substitutes for antibiotics due to the characteristics of nanomaterials and technologies, and have great development potential. Nanomaterials are a class of materials that have at least one dimension in the nanoscale (1-100nm) in three-dimensional space. They are composed of these basic units, including antimicrobial peptides, metal nanoparticles, semiconductors, polymer nanostructures and carbon-based nanomaterials. Carbon dots are a typical form of nanomaterials, consisting of sp 2 Hybrid carbon nanostructures in sp 3 The hybrid carbon matrix is composed of spherical nanoparticles with a diameter of less than 10nm. Carbon dots have multiple functional properties such as biocompatibility, photostability, low toxicity, easy synthesis, antibacterial, anti-inflammatory, antioxidant, and anticancer, and are widely used. However, there are still some challenges in the preparation of fluorescent carbon dots, such as cumbersome preparation steps, difficulty in obtaining some raw materials, insufficient antibacterial activity, and potential high toxicity.
[0003] As an important natural barrier, the skin can protect internal tissues from mechanical damage, limit water loss, and prevent pathogens from entering. However, the skin is often subjected to external damage, resulting in acute or chronic damage. The skin wound healing process is very complex and involves multiple stages, including hemostasis, inflammation, cell proliferation, tissue regeneration, repair of damaged tissues, restoration of function, and healing of the affected area. Traditional dressings have the problems of exacerbating the risk of infection, leading to poor blood circulation, and having weak mechanical properties, poor biocompatibility, poor biodegradability, low water absorption and retention, and high cytotoxicity, which limit their clinical application. The ideal wound dressing should have good biocompatibility, biodegradability, water absorption and retention, and no cytotoxicity. In recent years, hydrogels have been proven to be an ideal wound dressing that can achieve pain control and controlled drug release, promote wound repair and minimize scars. Carboxymethyl chitosan is a type of hydrogel, which is a chitosan derivative obtained by carboxymethylation. It has good biocompatibility and is widely used in gene therapy, drug delivery, and tissue engineering. However, in the existing technology, there are few studies on the development of carbon dots combined with hydrogels with simple preparation steps, easy-to-obtain raw materials, good antibacterial activity and low cytotoxicity as antibacterial materials and wound dressing materials for treating deep skin lesions, diabetic wounds and burns. Summary of the invention
[0004] The purpose of the present invention is to provide a zinc-doped antibacterial carbon dot and a preparation method and application thereof in order to solve the above problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] The present invention provides a method for preparing zinc-doped antibacterial carbon dots. Biomass and anhydrous zinc acetate are dispersed in deionized water according to a mass ratio, and a mixed solution is obtained after ultrasonic stirring. The mixed solution after hydrothermal reaction is naturally cooled, centrifuged, and filtered to obtain a carbon dot solution. The carbon dot solution is freeze-dried to obtain powdered zinc-doped antibacterial carbon dots.
[0007] As a further optimization scheme of the present invention, the biomass is corn stalk powder, and the mass ratio of the biomass to anhydrous zinc acetate is 1-3:1.
[0008] As a further optimization scheme of the present invention, the temperature of the hydrothermal reaction is 180°C-260°C, and the time is 2-6h; the centrifugal speed of the centrifugal treatment is 8000rmp, and the centrifugal time is 10-20min; the pore size of the filter membrane of the filtration treatment is 0.22μm.
[0009] The present invention also provides a zinc-doped antibacterial carbon dot, which is prepared by the above-mentioned preparation method of the zinc-doped antibacterial carbon dot.
[0010] The present invention also provides an application of zinc-doped antibacterial carbon dots in the preparation of antibacterial materials and wound antibacterial repair dressing materials.
[0011] As a further optimization scheme of the present invention, the antibacterial concentration of the zinc-doped antibacterial carbon dots is at least 100 μg / mL, and the bacteria are Gram-positive bacteria and Gram-negative bacteria.
[0012] As a further optimization scheme of the present invention, the antibacterial wound repair dressing material is a composite hydrogel.
[0013] The present invention also provides a method for preparing a composite hydrogel, wherein the zinc-doped antibacterial carbon dots, carboxymethyl chitosan, and bioactive glass are dissolved in double distilled water in proportion and stirred at room temperature to synthesize a zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel, i.e., a composite hydrogel.
[0014] As a further optimization scheme of the present invention, the mass ratio of the carboxymethyl chitosan, the bioactive glass, and the zinc-doped carbon dots is 400:5:1-16.
[0015] The beneficial effects of the present invention are:
[0016] The invention uses biomass as a carbon source and anhydrous zinc acetate as a dopant, and utilizes a one-step hydrothermal method to synthesize raw zinc-doped antibacterial carbon dots, wherein the zinc-doped antibacterial carbon dots have good antibacterial effects on both gram-positive bacteria and gram-negative bacteria. Subsequently, carboxymethyl chitosan, bioactive glass, and zinc-doped antibacterial carbon dots are used as raw materials, and the mixture is stirred at room temperature to synthesize zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel. The composite hydrogel has a simple preparation process, low cost, and low cytotoxicity. The zinc-doped antibacterial carbon dots have broad application prospects in antibacterial materials and in the treatment of deep skin lesions, diabetic wounds, and burn materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the preparation process of the composite hydrogel (i.e. zinc-doped antibacterial carbon-dot-based carboxymethyl chitosan hydrogel) of the present invention.
[0018] Figure 2 The characterization diagram and antibacterial performance test diagram of the zinc-doped antibacterial carbon dots of the present invention are shown in FIG. Figure 2 a is a transmission electron microscope image; Figure 2 b is the fluorescence spectrum; Figure 2 c is the UV-visible spectrum; Figure 2 d is the antibacterial results against Escherichia coli and Staphylococcus aureus; Figure 2 e is the biocompatibility diagram; Figure 2 f, 2g are SEM images before and after treatment of Staphylococcus aureus; Figure 2 h, 2i are SEM images of Escherichia coli before and after treatment).
[0019] Figure 3 a is the morphology of the composite hydrogel (zinc-doped antibacterial carbon point-based carboxymethyl chitosan hydrogel) of the present invention and its deformation when the finger is bent at different angles; Figure 3 b is a SEM image of the composite hydrogel of the present invention; Figure 3 c is a morphological diagram of the composite hydrogel of the present invention adhering to various material surfaces and body organ tissues.
[0020] Figure 4 a is a representative image of the wound surface changes over 12 days; Figure 4 b is a statistical graph of wound healing rate changing with time. DETAILED DESCRIPTION
[0021] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0022] 1. Materials
[0023] Unless otherwise specified, the methods used in this application are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0024] 2. Methods
[0025] 2.1 Preparation of zinc-doped antibacterial carbon dots-based carboxymethyl chitosan hydrogel
[0026] 2.1.1. Preparation of zinc-doped antibacterial carbon dots: corn straw powder and anhydrous zinc acetate were dispersed in deionized water according to the mass ratio, and ultrasonic stirring was performed to obtain a mixed solution; the mixed solution was placed in a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 240°C for 4 hours; the mixed solution after the hydrothermal reaction was naturally cooled, centrifuged at 8000 rpm for 15 minutes, and filtered through a 0.22 um filter membrane to obtain a carbon dot solution, and finally freeze-dried to obtain powdered zinc-doped antibacterial carbon dots;
[0027] The mass ratio of the biomass to anhydrous zinc acetate is 1-3:1;
[0028] It should be noted that the zinc-doped antibacterial carbon dot sample used in the following test was 0.5 g corn straw powder and 0.5 g anhydrous zinc acetate dispersed in 25 mL deionized water according to the mass ratio;
[0029] 2.1.2. Preparation of zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel: Dissolve the powdered zinc-doped antibacterial carbon dots, carboxymethyl chitosan and bioactive glass in double distilled water in proportion, and stir at room temperature for 6 hours to obtain zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel;
[0030] The mass ratio of the carboxymethyl chitosan, the bioactive glass, and the zinc-doped carbon dots is 400:5:1-16;
[0031] It should be noted that the zinc-doped antibacterial carbon dots-based carboxymethyl chitosan hydrogel sample used in the following test is 0.02 g zinc-doped antibacterial carbon dots, 8 g carboxymethyl chitosan, and 0.1 g bioactive glass dispersed in 100 mL double distilled water.
[0032] 2.2 Characterization and antibacterial performance evaluation of zinc-doped antibacterial carbon dots
[0033] 2.2.1 Characterization of Zn-doped Antibacterial Carbon Dots
[0034] The zinc-doped antibacterial carbon dots prepared in step 2.1 above were uniformly dispersed in water, showing good water dispersibility. Figure 2 From the transmission electron microscopy image of a, it can be seen that the zinc-doped antibacterial carbon dots are not standard spherical, and the particle size distribution is 1.5-5nm; Figure 2The fluorescence spectrum of zinc-doped antibacterial carbon dots solution is shown in the fluorescence spectrum of the typical carbon dots in the figure. In the excitation wavelength range of 300-380 nm, the fluorescence emission peak intensity of zinc-doped antibacterial carbon dots first increases and then decreases with the change of excitation wavelength, and the maximum emission spectrum is obtained at an excitation wavelength of 340 nm. Figure 2 The UV-visible spectrum of c shows the blue fluorescence emitted by zinc-doped antibacterial carbon dots under UV light.
[0035] 2.2.2 Evaluation of antibacterial properties of zinc-doped antibacterial carbon dots
[0036] The minimum inhibitory concentration (MIC) of the zinc-doped antibacterial carbon dots prepared in step 2.1 above against Staphylococcus aureus and Escherichia coli (with Escherichia coli as the model bacteria of Gram-negative bacteria and Staphylococcus aureus as the model bacteria of Gram-positive bacteria) was tested as follows:
[0037] Use PBS to dilute the bacterial solution to E. coli (1×10 6 CFU / mL) and Staphylococcus aureus (1×10 5 CFU / mL). The diluted bacterial solution was mixed with zinc-doped antibacterial carbon dot solution (final concentration was 0.8, 0.4, 0.2, 0.1, 0.05 mg / mL) in a 1:1 ratio, and the control group was cultured in a 37°C constant temperature incubator for 24 h with sterile PBS; then, 100uL of bacterial solution was evenly spread on LB solid agar plate and cultured in a 37°C constant temperature incubator for 24 h; finally, the plate was taken out and photographed, and the relative bacterial activity was obtained by counting the number of colonies.
[0038] Experimental conclusion: Taking Escherichia coli and Staphylococcus aureus as model bacteria for Gram-negative bacteria and Gram-positive bacteria respectively, the antibacterial effects of zinc-doped antibacterial carbon dot solutions on Escherichia coli and Staphylococcus aureus were shown as follows: Figure 2 d, as shown by Figure 2 d It can be seen that with the increase in the concentration of zinc-doped antibacterial carbon dots solution, the colony units of Escherichia coli and Staphylococcus aureus on the agar plates decreased significantly. It can be seen that zinc-doped antibacterial carbon dots have a good antibacterial effect on both Gram-negative and Gram-positive bacteria. The inhibitory concentrations of zinc-doped antibacterial carbon dots against Escherichia coli and Staphylococcus aureus are at least 100 μg / mL.
[0039] In order to determine the morphological changes of Escherichia coli and Staphylococcus aureus after being treated with the zinc-doped antibacterial carbon dots prepared in step 2.1 above, scanning electron microscopy observations were performed. Specifically, the zinc-doped antibacterial carbon dots solution (0.8 mg / mL) was added to Escherichia coli (1×10 6 CFU / mL) and Staphylococcus aureus (1×10 5CFU / mL) bacterial suspensions, all of which were incubated at 37°C for 8 h and then centrifuged at 5000 rpm for 5 min at 4°C. The bacteria were washed three times with 0.1 M PBS (pH 7.4), each time for 15 min, and fixed in 2.5% (v / v) glutaraldehyde solution for 2 h. Dehydrated with 30%, 50%, 70%, 80%, 90% and 100% ethanol for 10 min, respectively. After dehydration, the samples were dried with CO2 and sputtered with gold in an ion coating for 2 min. Finally, the morphology of bacterial cells was observed using a scanning electron microscope.
[0040] Experimental conclusion: In order to more intuitively compare the difference in cell membrane damage of gram-negative bacteria and gram-positive bacteria caused by zinc-doped antibacterial carbon dots solution, Escherichia coli was used as the model bacteria of gram-negative bacteria and Staphylococcus aureus was used as the model bacteria of gram-positive bacteria. The morphology of bacteria was observed by scanning electron microscopy. Figure 2 As shown in f and 2h, the bacterial structures of untreated Escherichia coli and Staphylococcus aureus (blank group) were intact, and the cell membranes were smooth and undamaged; Figure 2 As shown in Figures 2g and 2i, the SEM images of Escherichia coli and Staphylococcus aureus treated with 800 μg / mL zinc-doped antibacterial carbon dots solution showed that their cell morphology was incomplete, the cell membrane was damaged and wrinkled, and some cells even completely ruptured and the contents flowed out.
[0041] Cell viability assessment: According to the standard protocol, the toxicity of zinc-doped antibacterial carbon dot solution on 3T3 cells was detected by MTT method; 3T3 cells were inoculated in 96-well plates (blank wells of the wells were set as zero wells without cells) and cultured for 24 hours. Subsequently, the original culture medium was discarded, and then different concentrations of zinc-doped antibacterial carbon dot solution (final concentrations of 0, 50, 100, and 200 μg / mL) dispersed in PBS were added to the 96-well plate. Return to the incubator and continue incubation for 24 hours. The next day, the mixed culture medium was aspirated and the cytotoxicity was determined by MTT method. After 4 hours, 150 μL DMSO was added to the wells to dissolve the purple crystals at the bottom of the plate. The shaker was shaken at 150 rpm for 10 minutes to completely dissolve the crystals. Finally, the absorbance of the purple solution in the 96-well plate at 490 nm was detected by a microplate reader. In this experiment, 10 replicate wells were set for each concentration, and the test results were used to evaluate cell viability using statistical mean and standard deviation.
[0042] Experimental conclusion: Figure 2 As shown in e, Figure 2 e shows the viability of 3T3 cells after treatment with different concentrations of zinc-doped antibacterial carbon dots for 24 h. The cytotoxicity data show that different concentrations of zinc-doped antibacterial carbon dots do not harm cells and can promote cell proliferation to a certain extent. These data strongly indicate that zinc-doped antibacterial carbon dots exhibit low cytotoxicity and have great application potential in the antibacterial field.
[0043] 2.3 Performance evaluation of zinc-doped antibacterial carbon dots-based carboxymethyl chitosan hydrogel
[0044] The adhesion of zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel to various material surfaces and body organ tissues as well as the deformation of zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel when the finger is bent at different angles were tested.
[0045] Experimental conclusion: Figure 3 a, 3b show that the zinc-doped antibacterial carbon dots-based carboxymethyl chitosan hydrogel is completely transparent and exhibits an interconnected macroporous structure with pore sizes in this range, which promotes the proliferation and migration of epidermal cells; Figure 3 a and 3c show that the zinc-doped antimicrobial carbon dots-based carboxymethyl chitosan hydrogel can adhere to different surfaces such as skin, glass, Teflon, rubber and steel, showing a broad spectrum of adhesion. In addition, the hydrogel has high adhesion to biological tissues such as heart, liver, spleen, lung and kidney, which is crucial for biomedical applications. It was also found that the hydrogel has strong adhesion and can stretch / contract when the finger is bent, which is beneficial for wound repair.
[0046] The experiment used BALA / c5 male mice purchased from SPF (China) Hangzhou Ziyuan Experimental Technology Co., Ltd., with a body weight between 18 and 22 g. Under general anesthesia, the dorsal fur of these animals was removed with a depilatory cream. A deep full-thickness skin defect with a diameter of 8 mm was carefully created using a dermal biopsy punch. Then, 50 μL of bacterial suspension (Staphylococcus aureus, 1×10 6 CFUmL-1) and covered with sterile zinc-doped antibacterial carbon-dot-based carboxymethyl chitosan hydrogel and fixed with 3M tape; the untreated wound was used as the control; the wound recovery was recorded every 2 days; the wound healing rate was analyzed by comparing the wound area.
[0047] Experimental conclusion: Figure 4 a, 4b studied the effect of zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel dressing on full-thickness wound healing. The blank control group showed typical natural wound repair, and the zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel dressing significantly improved the progress of wound healing. After 12 days of treatment, the wounds of mice in the zinc-doped antibacterial carbon dot-based carboxymethyl chitosan hydrogel dressing group were completely healed, and compared with the natural wound repair, the healing speed was faster.
[0048] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing zinc-doped antibacterial carbon dots, characterized in that: Biomass and anhydrous zinc acetate are dispersed in deionized water according to a mass ratio, and a mixed solution is obtained after ultrasonic stirring. The mixed solution after hydrothermal reaction is naturally cooled, centrifuged, and filtered to obtain a carbon dot solution. The carbon dot solution is freeze-dried to obtain powdered zinc-doped antibacterial carbon dots.
2. The method for preparing zinc-doped antibacterial carbon dots according to claim 1, characterized in that: The biomass is corn stalk powder.
3. The method for preparing zinc-doped antibacterial carbon dots according to claim 1, characterized in that: The mass ratio of the biomass to anhydrous zinc acetate is 1-3:
1.
4. The method for preparing zinc-doped antibacterial carbon dots according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180°C-260°C, and the time is 2-6 hours; the centrifugal speed of the centrifugal treatment is 8000 rpm, and the centrifugal time is 10-20 minutes; the pore size of the filter membrane of the filtration treatment is 0.22 μm.
5. A zinc-doped antibacterial carbon dot, characterized in that: The method is prepared by the preparation method described in any one of claims 1 to 4.
6. Use of the zinc-doped antibacterial carbon dots as claimed in claim 5 in the preparation of antibacterial materials and wound antibacterial repair dressing materials.
7. The use according to claim 6, characterized in that: The antibacterial concentration of the zinc-doped antibacterial carbon dots is at least 100 μg / mL, and the bacteria are Gram-positive bacteria and Gram-negative bacteria.
8. The use according to claim 6, characterized in that: The wound surface antibacterial repair dressing material is a composite hydrogel.
9. A method for preparing a composite hydrogel, characterized in that: The zinc-doped antibacterial carbon dots, carboxymethyl chitosan and bioactive glass as claimed in claim 5 are dissolved in double distilled water in proportion and stirred at room temperature to synthesize the zinc-doped antibacterial carbon dots-based carboxymethyl chitosan hydrogel, i.e., the composite hydrogel.
10. The method for preparing the composite hydrogel according to claim 9, characterized in that: The mass ratio of the carboxymethyl chitosan, the bioactive glass and the zinc-doped carbon dots is 400:5:1-16.
Citation Information
Patent Citations
Method for quickly synchronously preparing lignin nano-particles and carbon quantum dots
CN108409984A
Carbon quantum dot fluorescent double-network hydrogel and preparation method and application thereof
CN111205484A
Preparation method of nano-enzyme hydrogel sheet and application of nano-enzyme hydrogel sheet in band-aid
CN113975459A
Antioxidant and antibacterial traditional Chinese medicine biomass carbon quantum dot nanogel as well as preparation method and application thereof
CN116942600A
Preparation method of sodium alginate hydrogel film containing nitrogen-doped carbon dots
CN118930912A